Total polyphenols and in vitro antioxidant activity of the aqueous extract of the bark of Brunfelsia grandiflora D. Don - Giraldo, Leonardo (2022)
Brunfelsia grandiflora D. Don “chiric sanango” is a plant native to the Peruvian Amazon, belonging to the Solanaceae and is used in traditional medicine by the jungle population. The objective of the research was to determine the content of total polyphenols and the in vitro antioxidant activity of the aqueous extract of its bark. The quantification of total polyphenols was carried out by applying the Folin-Ciocalteu method and the antioxidant activity by the method of elimination of free radical by electron transfer using 2,2-diphenyl-1-picrylhydrazyl (DPPH) the capacity method ferric reducing antioxidant (FRAP) and the hydrogen transfer method using 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS*†). The content of total polyphenols was 30,17 mg of gallic acid/100g of the extract and the antioxidant activity by the DPPH method was 11,86 mg Trolox/g sample; by the FRAP method it was 113,9 µmol of ascorbic acid equivalents/g sample and by the ABTS*† method it was 80,38 mg Trolox/g sample. Therefore, it can be concluded that the aqueous extract is an accessible source of antioxidants.